My Kidney Identity: Contextualizing pediatric patients and their families kidney transplant journeys. (21st July 2022) - Dunbar, Julia C.; Bascom, Emily; Pratt, Wanda; Snyder, Jaime; Smith, Jodi M.; Pollack, Ari H.
Abstract: Background: Even though having a kidney transplant is the treatment of choice for children with kidney failure, it can cause anxiety for patients and their families resulting in decreased psychosocial functioning, adherence, and self‐management. We set out to identify the information needs required to help pediatric patients and their families contextualize their posttransplant experiences as they recalibrate their understanding of normalcy throughout their transplant journey. Methods: Participants submitted photographs related to feeling: (1) worried, (2) confident, (3) similar to peers without kidney disease, and (4) different from these peers. The photographs served as a foundation for an in‐depth interview. Results: Nineteen individuals (10 pediatric transplant recipients and 9 caregivers) were interviewed at a mean of 8 years posttransplant. We identified five specific themes and tensions our participants associated with recalibrating their version of "normal" throughout the transplant journey: (1) exchanging information (information consumers vs. information contributors, (2) transitional management (family management vs. self‐management), (3) building confidence (worry vs. confidence), (4) telling one's story (hiding vs. self‐expression), and (5) normalizing kidney transplantation (feeling different vs. feeling similar). These five themes/tensions form one's Kidney Identity, shift from negative to positive throughout the transplant journey, illustrating a more abstract and complex account of kidney transplantation over time. Conclusions: Having a patient view their Kidney Identity over time may support self‐reflection of one's progress posttransplant and potentially help clinicians, patients, and their caregivers identify barriers and areas where they may need more support to ensure their successful engagement in their care.